The rock art of Huancha (Daniel Alcides Carrión - Pasco) and its implications in the interregional routes of central Peru during the Archaic and Formative periods - Palomino Gutiérrez, José (2024)
Huancha is an archaeological complex that presents a great variety of rock representations from different periods. In this paper we highlight its importance as a place of connection between the western side (the coast) and the eastern side (the Amazon basin) of the Andean mountain range, placing it within the discourse of recent research. We propose through the study of the rock art in Huancha that this site played an articu- lating role between different populations during the Archaic and Formative periods. In the Archaic period the site would be related to groups that practiced camelid hunting and began the process of domestication of these. During the Formative period it is related to the development of ceremonial activities and interactions, expressed in several conspi- cuous art styles and represented in a similar way to others located in the Coast and the Andes of central Peru, and even in some of the north. Based on these data, we consider that Huancha formed an important part of the interregional routes in an extensive area of the Central Andes that included the Amazon basin, and whose importance endures to the present day.